El turismo gastronómico y el crecimiento de los restaurantes de tres tenedores del distrito de Arequipa – 2019 - Romero Arce, Mishel Alicia (2022)
The purpose of this research was to be able to determine how gastronomic tourism favored the growth of three-fork restaurants in the district of Arequipa in 2019. The importance of this research is that it allows us to know the growth of this important item. business linked to tourist activity, such as that of three-fork restaurants, and the boost it receives from gastronomic tourism, research carried out in a pre-pandemic period, but whose information will help us to promote the reactivation of this important sector in the post-pandemic stage. _x000D_ Descriptive type research carried out with a sample of 52 interviewees among national and international tourists, members of the host community and entrepreneurs in the category of three-fork restaurants. The instruments used for the collection of information are the survey and interview questionnaire, the first applied to national and international tourists and members of the receiving community and to entrepreneurs in the category of three-fork restaurants, the second instrument corresponds to the competent authority of the tourism sector. _x000D_ The main conclusion reached by our research is that gastronomic tourism favored the growth of three-fork restaurants in the district of Arequipa - 2019, which confirms the veracity of our hypothesis.